Fish domestication Tapah (Wallago leeri) With different Stocking Densities - Tang, Usman M; ', Padli; ', Mulyadi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2015)
The research was conducted on Date 26 February - 12 April 2015 in Aquafarm Hatchery Park road work, Pekanbaru. Objectives and Benefits Research husband was to determine the growth and survival of fish tapah (Wallago leeri) Solid stocking. Methods Used hearts Research husband is experimental method and RAL with three treatments and three replications, treated hearts Research husband is P1 3 heads / 60liter, 4 tail P2 / liter, P3 tail 5 / liter. Results indicate that stocking Solid 4 head / liter. Absolute growth rate of fish tapah highest weight 39.91 grams, length 2,34 cm Absolute, daily growth rate of 1,07%. Keywords: Growth, survival, Tapah (wallago leeri), Stocking Density